Consumptive use of water, A factor in determining irrigation planning - Dabral, B.G. (Journal of Soil and Water Conservation, 2022)
Consumptive use of water (evapotran- spiration) is an important factor in irrigation planning. A knowledge of irrigation emciency and interrelationship between soil water and crop plants would prove very helpful in understanding the time and needs of irrigation. The soils should be classified with respect to their water absorbing, water retaining and water releasing properties. The relationship between soil moisture and fertilizers as well as the root zone depth and moisture extraction by different crops should be worked out. The peak consumptive use rates of crops is very important factor and should not be overlooked in designing irrigation system. The climatological data of a locality may be used for calculating water needs for irrigation.